Peran infografis sebagai media promosi dalam pemanfaatan perpustakaan - Ajeng Resnatika; Sukaesih Sukaesih; Nuning Kurniasih (Jurnal Kajian Informasi dan Perpustakaan, 2018)
Infographics are visualizations of data, ideas, information or knowledge through charts, graphs, schedules, and others so that data, ideas, information or knowledge can be presented more than just text and have a visual impact that is quite strong and more interesting. The study was conducted at the Bandung Institute of Technology Library and was aimed to determine the role of infographic’s attractiveness, clarity, and ease of understanding in utilizing library services at the Bandung Institute of Technology Library. This study used a quantitative descriptive analysis method, and the population in this study was library visitors totaling 13,716 people. Samples were obtained using the random sampling technique with a total of 100 people. The results of this study indicated that infographics as a promotional medium played a role in library utilization with indicators namely infographic attractiveness, clarity, and ease of understanding. The conclusions are that infographics play a role as promotional media in library utilization: seen from the aspect of attraction, the presentation of content on infographics attract the attention of the reader with display of colors and images that attract the reader; from the aspect of clarity, the information presented is precisely the content on the infographics for readers with font and the suitability the image; from the aspect of ease of understanding, the reader easily understand the information contained in the infographics so the reader can interpret for the meaning the message in this infographics.